Analisis Pengendalian Kualitas Produk Jendela Kayu Menggunakan Metode Fault Tree Analysis (FTA) dan Failure mode And Effect Analysis (FMEA) pada CV Arafah Jaya Purwakarta - Wahyudi, Hafizh Nur; Ulum, Rikzan Bachrul; Wibowo, Priyo Ari (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the quality control of wooden window products at CV Arafah Jaya Purwakarta, which recorded a defect rate of 22%. The Fault Tree Analysis (FTA) method is used to identify root causes of failures, while the Failure mode and Effect Analysis (FMEA) method prioritizes corrective actions based on the Risk Priority Number (RPN). Data were collected through observation, interviews, and documentation from January 2024 to February 2025. The analysis identified five main defect types: brittle wood, imprecise joints, incorrect dimensions, insect infestation, and peeling paint. Brittle wood had the highest RPN value (315), making it the top priority for improvement. Corrective suggestions were formulated using the 5W+1H approach to develop systematic solutions. The combined application of FTA and FMEA proved effective in reducing defect potential and improving product quality.